Intramolecular Diels-Alder reactions of cycloalkenones: stereoselectivity, Lewis acid acceleration, and halogen substituent effects. - Pham, H; Paton, R; Ross, A; Danishefsky, S; Houk, K (2014)
The intramolecular Diels-Alder reactions of cycloalkenones and terminal dienes occur with high endo stereoselectivity, both thermally and under Lewis-acidic conditions. Through computations, we show that steric repulsion and tether conformation govern the selectivity of the reaction, and incorporation of either BF3 or α-halogenation increases the rate of cycloaddition. With a longer tether, isomerization from a terminal diene to the more stable internal diene results in a more facile cycloaddition.